Histological and biochemical effects of cigarette smoke on lungs - Ozan, Enver; Kükner, A.; Canpolat, L.; Öner, H.; Gezen, M.R.; Yilmaz, S.; Ozan, S. (My University, 2001)
In this study, rats were made to inhale cigarette smoke in a specifically prepared container for different periods. The lung tissue samples of the subjects were examined by light microscopy, transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Malonaldehyde, one of the free oxygen radicals was determined in lungs and plasma. The catalase activity level of erythrocyte and arginase levels were determined. Three groups were formed. The rats in the Ist and IInd groups were made to inhale cigarette smoke for 30 and 60 minutes a day for a total period of 3 months. Control group, the rats in the IIIrd group (controls) were made to inhale clean air during the same periods. An increase in the number of macrophages was observed in the pulmonary tissue of the exposed groups. Especially in the group that inhaled the smoke for long periods, the number of macrophages and the inclusion bodies contained in them increased. These differences could easily be observed in TEM studies. In the light microscopy and SEM observations, it arouse attention that the alveolar macrophages occurred as sets and their activation increased. Depending on the length of the exposure to cigarette smoke, an increase in the number of macrophages was observed. Statistically significant increases were determined in the malonaldehyde levels of pulmonary tissue and plasma when compared to the control group. Besides significant increases were found in the catalase activity levels of erythrocytes in the experimental groups.
Keywords: Catalase; Cigarette; Lung; Malonaldehyde; SEM; TEM